Muhammad and Islam - Marchant, Kerena (ManKato, MN : Smart Apple Media, 2002)
An introduction to the religion of Islam and to its prophet, Muhammad.
Keywords: Muhammad, -- Prophet, -- d. 632 -- Juvenile literature; Muhammad, -- Prophet, -- d. 632.; Muslims -- Saudi Arabia -- Biography -- Juvenile literature; Prophets; Islam